2011
DOI: 10.3109/01443615.2011.567342
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after rupture of the pregnant uterus

Abstract: Pregnant women managed by us after suture repairs for rupture of the pregnant uterus between 2006 and 2009 in Enugu, South-east Nigeria were reviewed. Five pregnancies were managed during the study period. Four had normal pregnancies. Three booked early in pregnancy and had repeat caesarean deliveries at 36 weeks' gestation. One booked at another private hospital but had emergency caesarean section at 38 weeks' gestation. The fourth woman had repeat rupture at 28 weeks' gestation, suture repair and bilateral t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Overall, the risk of perinatal death was of 3.4% (26/776) with rates ranging between 0.9% (one case over 109 pregnancies, Thisted et al 19 ), and 20% (one case out of five reported, Okafor et al 22 ). Perinatal death was almost exclusively due to a repeat uterine rupture with the fetus stillborn.…”
Section: Resultsmentioning
confidence: 97%
“…Overall, the risk of perinatal death was of 3.4% (26/776) with rates ranging between 0.9% (one case over 109 pregnancies, Thisted et al 19 ), and 20% (one case out of five reported, Okafor et al 22 ). Perinatal death was almost exclusively due to a repeat uterine rupture with the fetus stillborn.…”
Section: Resultsmentioning
confidence: 97%
“…Thirteen articles were found [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] (references [31] and [32] reported the same cases). Full-text articles reporting about subsequent fertility and pregnancy after complete uterine rupture were retrieved.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The search for this period yielded seven case reports of 1-22 patients [30][31][32][33][34][35][36][37]. Table 2 summarizes these seven reports.…”
Section: Review Period 1971-2005mentioning
confidence: 99%
“…The article by Okafor et al (2011) describes successful management of five pregnancies after the uterus had ruptured in an earlier pregnancy and had been repaired using chromic catgut No. 2 gauge in two layers.…”
Section: A B Macleanmentioning
confidence: 99%